4CPS-074 Impact of antibiotic prophylaxis guidelines in obstetric and gynaecology surgery: a retrospective multi-centre study. (2nd March 2018) - Panciroli, C; Davies, SE Campbell; Dragonetti, MM; Luoni, A; Muserra, G; Patrizia, T; Bignamini, A; Minghetti, P
Abstract : Background: Antibiotic prophylaxis in obstetrics and gynaecology (O and G) surgery is known to be effective in reducing postoperative infections, hospitalisation and costs. In 2008, local guidelines on antibiotic prophylaxis in surgery were published as a result of a multidisciplinary work group (including hospital pharmacists) which involved seven hospitals in the Lombardy Region. However, guidelines give general indications and the implementation into clinical practice is not always efficient. Purpose: To evaluate the impact of the introduction of local guidelines on antibiotic prophylaxis in elective O and G surgery 7 years after implementation. Material and methods: A multi-centre retrospective study was conducted involving three centres which had implemented the guideline in 2008 and was still in use. Medical records of patients undergoing elective surgical procedures in 2006 (pre-guideline) and 2015 (post-guideline) were reviewed by collecting data about patients, surgeries, postoperative infections and antibiotics. Data, collected from medical records, were transferred to a specifically designed database application in Filemaker Pro. Statistical analysis was performed by using SPSS and R. Comparisons were analysed using Chi square tests, multivariable logistic regression and analysis of variance. The effect estimate was reported in risk ratio (RR) and pooled using a random effects model. Results: A total of 585 patients who underwent elective O and G procedures (caesarean section and vaginal hysterectomy) were analysed: 304 procedures for 2006 and 281 surgeries for 2015. 'Adequate' antibiotic prophylaxis substantially changed after guideline implementation (RR 1. 21; 95% CI: 1.14 to 1.29, p<0.001): variation was more significant in elective caesarean section (hysterectomy vs. caesarean section: OR 4.059, 95% CI: 2.028 to 8.126, p<0001). Guideline implementation has resulted in an important improvement in terms of compliance to all elements of antibiotic administration: selection (7.2% for 2006 and 56.9% for 2015), dosing (20.4% for 2006 and 84.6% for 2015) and duration of prophylaxis (57.6% for 2006 and 81.5% for 2015). Conclusion: Our data suggest that the introduction of the local guideline on antibiotic prophylaxis in surgery substantially improved the use of antibiotics in O and G units 7 years after publication. The success of the guideline implementation could have been influenced by the active participation of hospital pharmacists in periodically training healthcare workers and auditing after publication. No conflict of interest